Male harassment leads to fitness costs for females by disrupting oviposition site preferences. (14th February 2020) - Bacon, Elisabeth; Barbosa, Flavia
Abstract: In many species, a difference in the optimal number of copulations for males and females leads to sexual conflict. This is well documented in the bean beetle Callosobruchus maculatus, where both sexes mate multiply and females incur fitness costs from injuries caused by the male genitalia. Here, we demonstrate that sexual conflict also decreases female fitness due to male harassment. We hypothesized that harassment costs would come as 1) decreased clutch size, egg size, or both and by 2) disruption of female preference for higher-quality oviposition substrate. Mated females were housed with two bean types—cowpeas, their preferred natal hosts, and toxic pinto beans. They were then submitted to either no, moderate, or high male harassment in the oviposition site. Females under harassment produced smaller clutch sizes but not smaller eggs, resulting in the absence of an egg-size/clutch-size trade-off. Additionally, females did not exhibit a preference for their natal cowpeas hosts over toxic pinto beans when males were present at the oviposition site, although they do so when harassing males are not present. Harassment disrupted female responses to variation in oviposition substrate quality, resulting in considerable fitness consequences in the form of lower offspring production and survival. Abstract : Male harassment in bean beetles leads to significant fitness consequences for females: when harassed, females produce fewer eggs and stop exhibiting an adaptive preference for higher-quality substrates for egg laying. As offspring are confined to this substrate until adulthood, this loss of preference has a major impact in larval development and mortality. Overall, females under male harassment had lower offspring production and survival.